TINJAUAN HISTORIS ILMU HADIS DAN KODIFIKASINYA - Amirudin; Fitriyadi, Muhammad; Yuliharti (Sekolah Tinggi Ilmu Al-Qur'an (STIQ) Ar-Rahman, 2023)
The science of hadith is a scientific discipline that studies hadith, whether it is narrators, sanad, or everything related to hadith, hadith is the second source of law after the Qur'an. Hadith is everything that is based on Rasulullah SAW, be it actions, words and decrees. Historically the development of the science of hadith has several first processes starting from the prophetic period to the tabi'tabi'in. This article will discuss the history of the development of hadith science and its codification, the method the author uses in writing this article is the library research method with how to collect data in the form of journals, books, and other documents related to hadith. Historically, the hadith was only recorded in the 2nd century H